Extraordinary forms of aging : life narratives of centenarians and children with progeria - Velten, Julia (Aging studies, 2022)
While aging and the life-course appear to be normalized processes, the complex construction of age at the intersection of biology, society, and culture remains opaque. This study contributes to a deeper understanding of age(ing) by exploring its construction through the analysis of extraordinary cases. Focusing on life narratives of centenarians and children with progeria, Julia Velten analyzes the way in which these people experience age(ing) and shows how these experiences can contribute to our understanding of age. Situated at the intersection of aging studies and medical humanities, the study explores what extraordinary age(ing) can tell us about aging processes in general.